ANALISIS PROSES BERPIKIR KREATIF SISWA DITINJAU DARI GAYA KOGNITIF BERDASARKAN TEORI WALLAS - Listiyana Putri, Yohana Daning; ,, Sutriyono; Pratama, Fika Widya (Jurnal Karya Pendidikan Matematika, 2019)
The purpose of this study is to know the process of creative thinking of students according to the theory of Wallas, and reviewed of the cognitive style of psychology. The type of this research is descriptive qualitative. The subject in this study amounted to 6 students from SMP Kristen 2 Salatiga, which consisted of 3 students with cognitive style Field Independent (FI), and 3 students with cognitive style Field Dependent (FD). The subject taking technique is a purposive sampling. Based on the results of analysis and discussion, the subject of FI can carry out all stages of the process of creative thinking according to Wallas's theory (preparation, incubation, illumination, verification) well, compared to the subject of FD.